Estimating the Size of the Human Trafficking Problem: MSE and Other Strategies. (December 2021) - Zhang, Sheldon X.; Larsen, Jacqueline Joudo
The prevalence of human trafficking has remained as elusive as the method of producing its estimation is contested. There are significant variations in the way prevalence estimation is produced, with some methods garnering more attention than others. To complicate the issue further, the hidden nature of human trafficking makes it difficult to apply conventional probability-based sampling strategies, without which for reference purposes one cannot easily assess the merits of alternative estimation techniques. This special issue represents the most recent development and applications of one particular method, the multiple systems estimation (MSE) method. Although we remain biased towards primary data for prevalence estimation, MSE represents a cost-effective alternative for the purposes of advocacy, policymaking, and victim services.